2013
DOI: 10.1111/1442-1984.12004
|View full text |Cite
|
Sign up to set email alerts
|

Does community‐level floral abundance affect the pollination success of a rewardless orchid, Calanthe reflexaMaxim.?

Abstract: Decreases in pollinator abundance may particularly constrain plants that lack floral rewards, since they are poor competitors for pollinators in the plant community. Here, we documented the pollination ecology of a rewardless orchid, Calanthe reflexa Maxim., and examined effects of forest understory degradation by deer browsing on pollination success of the species in the light of a change in the abundance of neighboring flowering plants in 2010 and 2011. Bombus species were the only pollinators at each site a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…The floral spur of C. yaoshanensis contains no nectar, as in the five insect‐pollinated Calanthe spp. studied previously (Zhang et al ., ; Sugiura, ; Sakata et al ., ; Suetsugu & Fukushima, ). The flower of C. yaoshanensis shows much the same suite of floral characters as described in many other epidendroid species that are food mimics and are pollinated by large insects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The floral spur of C. yaoshanensis contains no nectar, as in the five insect‐pollinated Calanthe spp. studied previously (Zhang et al ., ; Sugiura, ; Sakata et al ., ; Suetsugu & Fukushima, ). The flower of C. yaoshanensis shows much the same suite of floral characters as described in many other epidendroid species that are food mimics and are pollinated by large insects.…”
Section: Discussionmentioning
confidence: 99%
“…distributed in Japan was also extremely low, ranging from 0–9.0% in C. reflexa Maxim. (Sakata et al ., ) to 8.3–17.3% in C. striata Lindl. (Sugiura, ), 1.20–6.49% in C. discolor (Suetsugu & Fukushima, ) and c .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Yumoto & Matsuda ), which consequently caused negative indirect effects on plant reproduction through cascading effects of pollination linkages (Vazquez & Simberloff ; Sakata et al . ; Sakata & Yamasaki ). Recent studies have found that at sites with severe deer browsing, the visitation rate of bumblebees decreased because of severe reductions in the coverage of autumn‐flowering herbaceous plants (Kato & Okuyama ; Okuda et al .…”
Section: Introductionmentioning
confidence: 99%